2010
DOI: 10.1007/s10661-010-1800-1
|View full text |Cite
|
Sign up to set email alerts
|

Mercury contamination in human hair and some marine species from Sfax coasts of Tunisia: levels and risk assessment

Abstract: The aim of this study was to measure the mercury (Hg) contents of three marine fish and common seafood species (Diplodus annularis, Sarpa salpa and Sepia officinalis) at two sampling sites in the gulf of Gabes, i.e. Sidi Mansour (polluted site) and Kerkennah (control site). These species are frequently consumed by the population living at the Sfax coasts of Tunisia, particularly by the families of fisherman. Additionally, the hair mercury levels of 55 volunteers (28 women, 27 men) were analysed and the daily t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 36 publications
2
15
0
Order By: Relevance
“…Thunnus spp., Xiphias gladius), studies focusing on mercury concentrations in teleostei fish, including Sparidae and Balistidae, are much scarcer (Türkmen et al 2008;Mezghani-Chaari et al 2011). As expected, the values obtained in the present study revealed that the omnivorous species (B. capriscus) accumulates much more mercury than the herbivorous species (S. salpa).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Thunnus spp., Xiphias gladius), studies focusing on mercury concentrations in teleostei fish, including Sparidae and Balistidae, are much scarcer (Türkmen et al 2008;Mezghani-Chaari et al 2011). As expected, the values obtained in the present study revealed that the omnivorous species (B. capriscus) accumulates much more mercury than the herbivorous species (S. salpa).…”
Section: Discussionsupporting
confidence: 77%
“…As expected, the values obtained in the present study revealed that the omnivorous species (B. capriscus) accumulates much more mercury than the herbivorous species (S. salpa). Mezghani-Chaari et al (2011) also analysed the mercury concentration in the edible parts of two Sparidae fish (Diplodus annularis and S. salpa) from Sidi Mansour (12 Km to the north of Sfax) and reported mean concentrations of 1100 and 80 ppb wet weight, respectively. The value obtained in S. salpa by the latter authors is very similar to that observed in the present study (74.9 ppb) in the muscle of cow breams from Sfax whereas the level of mercury reported in D. annularis was higher than the herein reported in B. capriscus from Sfax (212 ppb).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there have been a number of investigations on the impacts of pollutants such as hydrocarbons and nutrients (e.g., phosphate, nitrate, ammonium), total polyphenolic compounds and phosphogypsum wastes in the Sfax coast (e.g., [40,43,44]), the human and ecological risk from pollutants, namely heavy metals, have not yet been investigated in the gulf of Gabes. Indeed, the coastal zone of Sfax has been subjected to some investigations on trace metals in sediments [45] or in some seafood such as annular sea bream fish (Diplodus annularis), cow bream (Sarpa salpa), and cuttlefish (Sepia officinalis) [46], and in the marine bivalve Ruditapes decussatus [47][48], but data on the spatial distribution of dissolved trace metals in the surface seawater are scarce or absent.…”
Section: Introductionmentioning
confidence: 99%
“…The Gulf of Gabès locates in the south-eastern coast of Tunisia. It is characterized by shallow waters, important tidal activity, high temperature, and high salinity (Ladhar-Chaabouni et al 2012;Mezghani-Chaari et al 2011). This marine ecosystem is threatened by pollution from industrial activity developed along the coast.…”
Section: Introductionmentioning
confidence: 99%